2016
DOI: 10.1186/s12865-016-0171-y
|View full text |Cite
|
Sign up to set email alerts
|

Plasma fetuin-A/α2-HS-glycoprotein correlates negatively with inflammatory cytokines, chemokines and activation biomarkers in individuals with type-2 diabetes

Abstract: BackgroundFetuin-A/AHSH is a novel hepatokine that acts as a vascular calcification inhibitor and as an endogenous TLR-4 ligand. Fetuin-A may act as a positive or negative acute phase protein (APP) in disease conditions. The relationship between circulatory fetuin-A and inflammatory biomarkers in type-2 diabetes (T2D) remains controversial. Therefore, the purpose of this study was to determine the plasma fetuin-A levels in 53 T2D (BMI = 29.7 ± 4.5 kg/m2) and 72 non-diabetic individuals (BMI = 28.2 ± 5.8 kg/m2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…Sindhu and cols. demonstrated a negative correlation between plasma levels of fetuin-A and systemic inflammatory markers in patients with type 2 diabetes (4). Serum levels of fetuin-A increase mid-trimester in normal pregnancies (5).…”
Section: Introductionmentioning
confidence: 93%
“…Sindhu and cols. demonstrated a negative correlation between plasma levels of fetuin-A and systemic inflammatory markers in patients with type 2 diabetes (4). Serum levels of fetuin-A increase mid-trimester in normal pregnancies (5).…”
Section: Introductionmentioning
confidence: 93%
“…In the current study, consideration of all groups simultaneously showed a negative and significant correlation between the total amount of fetuin‐A and SAA, TNF‐ α , CAL, and GI. There is evidence that fetuin‐A is negatively associated with systemic inflammatory mediators (Sindhu et al , ). To evaluate the relationship between fetuin‐A and inflammatory markers, we examined the correlations between fetuin‐A, TNF‐ α , and SAA.…”
Section: Discussionmentioning
confidence: 99%
“…Fetuin-A levels reveal a divergent correlation with pro-in ammatory markers in patients with T2DM. The investigation of in ammatory mediators or activation markers in T2DM patients by Sindhu et al (2016) demonstrated a reciprocal correlation between plasma levels of fetuin-A and interleukin (IL)-1 , IL-7, IL-15, tumor necrosis factor alpha (TNF-), chemokine ligand (CCL)-2, CCL4, soluble CD40L (sCD40L), growth related oncogene (GRO), elongation factor F (EFF) 2, and vascular endothelial growth factor (VEGF) [31]. The study provided evidence that fetuin-A levels are reciprocally associated with the pro-in ammatory cytokines and biomarkers that possess a predictive value of fetuin-A as a negative acute phase protein in patients with T2DM.…”
Section: Fetuin-a Role In Increased Risk Of T2dmmentioning
confidence: 99%